Analysis of scientific provisions of resource concepts in economic theory and theory of strategic management - Loishyn, Anatolii (Social Development and Security, 2021)
The article summarizes the arguments and counterarguments in a scientific discussion on the development of a modern concept of resource support for the security and defence sector of Ukraine. The aim of the study is to analyze the economic theory and the theory of strategic management on the presence of theoretical provisions on the transformation of the content of the economic category “resources” and resource concepts for understanding their scientific content, and development prerequisites for the development of a modern concept of resource provision for the security and defence sector of Ukraine. Based on the systematization of literary sources and approaches to solving the problem of resource support for the security and defence sector of Ukraine, it is determined that there are approaches in economic theory and the theory of strategic management that can be used in further studies of the subject area. The urgency of solving this scientific problem is confirmed by the measures initiated by the state leadership in accordance with the conceptual documents of state administration and defence planning. The subject plane in the article is investigated in the following logical sequence: economic theory is analyzed, then – the theory of strategic management, conclusions are formulated. Analysis, synthesis, decomposition, and the historical method became the methodological tools of the study. The study presents the results of an empirical analysis of economic theory and the theory of strategic management, namely, it is noted that in the course of developing a modern concept of resource support for the security and defence sector, it is necessary to take into account the main categories of the resource concept: resources, abilities, competencies, organizational routine. The study empirically confirmed and theoretically proved that the issues of scientific research of resources as an economic category and operations with them have been relevant since the time of Aristotle, which is confirmed by the constant search for mechanisms for their optimal use, taking into account the limiting factor. The results of the study can be useful for scientists and managers studying the issues of comprehensive support in the field of the security and defence sector of Ukraine.